2017
DOI: 10.18632/oncotarget.15823
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant methioninase effectively targets a Ewing's sarcoma in a patient-derived orthotopic xenograft (PDOX) nude-mouse model

Abstract: Methionine dependence is due to the overuse of methionine for aberrant transmethylation reactions in cancer. Methionine dependence may be the only general metabolic defect in cancer. In order to exploit methionine dependence for therapy, our laboratory previously cloned L-methionine α-deamino-γ-mercaptomethane lyase [EC 4.4.1.11]). The cloned methioninase, termed recombinant methioninase, or rMETase, has been tested in mouse models of human cancer cell lines. Ewing's sarcoma is recalcitrant disease even though… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 49 publications
1
62
0
Order By: Relevance
“…Methionine calculation. Methionine was determined with an HPLC procedure described previously (28,29).…”
Section: Methodsmentioning
confidence: 99%
“…Methionine calculation. Methionine was determined with an HPLC procedure described previously (28,29).…”
Section: Methodsmentioning
confidence: 99%
“…We also showed that recombinant methioninase (rMETase) suppressed ES PDOX growth by lowering the blood methionine (MET) and the intra-tumor MET level [24]. However, neither treatment regressed the ES PDOX.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, PDOX models of sarcoma (47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64), cervical cancer (65-67) as well as melanoma (68)(69)(70)(71)(72)(73)(74) have also been developed.…”
Section: Patient-derived Orthotopic Xenograft (Pdox) Mouse Models Of mentioning
confidence: 99%